RISK FACTORS FOR HYPERTENSION DURING PREGNANCY AT THE MOTHER RINI CLINIC, SUNGGAL DISTRICT, MEDAN CITY NORTH SUMATRA PROVINCE 2024 - Anisa Zamna , Laila; Imran Saputra Surbakti; Mesrida Simarmata; Syamsuarni; Zahara Herani; Dea Nuarista Parangin-angin; Iqra Manisah, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Introduction: Hypertension in pregnancy is a very dangerous condition if it occurs in pregnant women because it can cause preeclampsia, preterm birth, fetal growth disorders, respiratory syndrome and fetal death. Objective: to analyze the incidence of hypertension in pregnancy at the Bunda Rini Clinic in 2024. Population and Sample: all pregnant women who came to visit the Bunda Rini Clinic during 2023 as many as 30 pregnant women. with a total sampling technique of 30 people. Place and time: at the Sally Clinic, Tembung on month April– July 2024. Results : Univariate : majority age 20-335 year as many as 18 people (60%) people, the majority of high school education as many as 15 people (50%), the majority of housewives as many as 28 people (88.8%), parity as many as 21 people (70%). Bivariate: Respondents suffering from pregnancy hypertension came from ages > 20 years and > 35 years. The chi square statistical test is p value = 0.000. The Relationship of Nutrition with Pregnancy Hypertension of 8 people (27%) pregnant women with pregnancy hypertension, the majority with malnutrition as many as 6 people (20%), the chi square statistical test is p value = 0.018 then the P value of age and nutrition is the same < 0.05 indicates there is a relationship between age and nutrition with the incidence of hypertension. In terms of parity as many as 8 people (27%) with the majority of multiparous parity. The chi square statistical test is p value = 0.363 which This means that p>0.05 indicates that there is no relationship between the incidence of hypertension and the incidence of pregnancy hypertension. Conclusion: There is a relationship between age and nutrition in the incidence of hypertension and there is no relationship between parity and the incidence of pregnancy hypertension.